The impact of underutilised crops as feed and food ingredients - Bone, Gabrielle M (2023)
In the face of population growth and climate change, alternative feed sources are urgently needed to replace traditional sources such as soybean and wheat. The bambara groundnut and mezquite trees are two underutilised crops of current interest but are underutilised due to lack of widespread knowledge on cultivation or potential uses.